Quality and Safety Profile of Chili Sauce in Cirebon City - Salwa Oksiputri Aulia (CV. Publikasi Indonesia, 2026)
The quality and safety standards of chili sauce are determined in SNI 01-2976-2006. It states that if chili sauce is not handled and processed properly, it can be contaminated with hazardous substances that cause disease or poisoning, such as Rhodamine B. Long-term consumption of Rhodamine B may lead to liver dysfunction or malignancy. To observe the quality and safety of chili sauce based on its characteristics and to identify the use of Rhodamine B dye in chili sauce sold with snacks around Bima Stadium. This study was conducted descriptively using a qualitative laboratory approach at the Research Laboratory of Swadaya Gunung Jati University. Sampling was carried out using total sampling from food vendors around Bima Stadium, Cirebon City, who met the inclusion criteria. Samples were examined for chili sauce characteristics in terms of aroma, appearance, and color and tested for Rhodamine B content using the Rhodamine B Rapid Test Kit (Labtest Reagent®). Data were obtained from 18 samples, analyzed descriptively, and presented in tables accompanied by narrative explanations. Of the 18 samples, 2 samples (11.1%) of chili sauce tested positive for Rhodamine B, while 16 samples (88.9%) were negative. Abnormal aromatic characteristics were found in 3 samples (16.7%), whereas 15 samples (83.3%) were normal. Based on appearance, 4 samples (22.2%) were abnormal and 14 samples (77.8%) were normal. In terms of color, 2 samples (11.1%) were abnormal and 16 samples (88.9%) were normal. Rhodamine B and abnormal physical characteristics were found in some chili sauce samples.